(untitled) (UUM Journal of Legal Studies, 2021)
Climate change has always been an agenda for the international community, individually and collectively, due to global warming and unusual weather conditions. The International Renewable Energy Agency (IRENA) believes that the adequate deployment of clean energy can achieve the targets of the Paris Climate Change Agreement. Many countries have shown their commitment to decrease their carbon emission levels substantially, and they have done so by resorting to renewable energy sources. Renewable energy generation opens a viable door for climate change mitigation efforts. Both Malaysia and India are committed to fulfilling their obligation under the Paris Agreement. This comparative study evaluates the laws and policies related to renewable energy in Malaysia and India, as these countries progress towards their commitments under the Climate Change Convention (UNFCCC). This study operates under the comparative qualitative methodological framework and utilises secondary sources for analysis. Based on the comparative expositions, Malaysia can learn measures adopted by India to accelerate renewable energy development as well as to reduce greenhouse gas (GHG) emission, which will prove beneficial to the country as well as in order to comply with international conventions and agreements.